Penggunaan Sistem Pembayaran QRIS Sebagai Alat Transaksi non Tunai terhadap Perkembangan UMKM Binaan Bank Indonesia Provinsi Gorontalo - Koni, Wiwin; Sofhian; Ismail, Juniaty; Niswatin; Halid, Rahmawati (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This research aims to determine the impact of using the QRIS payment system as a non-cash transaction tool on the development of MSMEs assisted by Bank Indonesia in Gorontalo Province. This research method uses quantitative research methods, the sample taken was 101 MSME respondents who were MSMEs assisted by Bank Indonesia, the sampling technique used in this research was a saturated sampling technique. The results of this research show that the QRIS payment system has an influence on the development of MSMEs under the guidance of Bank Indonesia Gorontalo, so consistency in the use of payments via QRIS is needed so that MSMEs understand banking technology more and make it easier for MSMEs to carry out payment transactions. The suggestions in this research are encourage Indonesian banks to further expand their MSME development so that more and more MSME players are aware of QRIS technology in banking